Composite Right- and Left-Handed Traveling-Wave Field-Effect Transistors - Koichi Narahara (Active and Passive Electronic Components)
We introduce a composite right- and left-handed travelling-wave field-effect transistor (CRLH TWFET) for developing large-scale platform to support left-handed waves. The device represents two electromagnetically coupled CRLH transmission lines by capacitance and FET transconductance. Owing to the couplings, two different modes can support waves in CRLH TWFETs. It was experimentally established that waves supported by one of the modes were amplified, while those supported by the other mode were significantly attenuated. To quantify the wave propagation in CRLH TWFETs, we developed a numerical model based on the transmission line theory that well simulated measured results. This paper discusses the results of numerical calculations that validate the design criteria of CRLH TWFETs.